γ-Radiation-assisted molecular template route: a new hybrid path for facile synthesis of size-dependent optical properties of ZnS quantum dots - Sanju Francis; Nisha Kushwah; Vishwanadh Bathula; Kedarnath Gotluru (Royal Society Open Science)
ZnS is a benign and multi-utility semiconductor with absorption in the UV–vis region of the energy spectrum. Nevertheless, the synthesis of ZnS quantum dots (QDs) with tunable optical properties and a reasonable photoluminescent quantum yield (PLQY) adopting a new hybrid method is highly recognized. The present study involves the simple synthesis of self-capped wurtzite ZnS QDs employing a hybrid method comprising a single-source molecular precursor (SSMP), 2-(dimethylamino)ethanethiolate of zinc(II), and γ-radiation followed by elucidation of the formation mechanism of self-capped ZnS QDs. Here, the SSMP has been γ-irradiated in a solution to yield ZnS QDs of varying size at different radiation doses. The crystal structure, elemental composition, shape and optical properties of pristine self-capped ZnS QDs were assessed by powder X-ray diffraction, energy dispersive X-ray spectroscopy, electron microscopy, UV–vis, photoluminescence and diffused reflectance spectroscopy, respectively. The size-tailored emission maximum and optical band gaps were tweaked to a tune of 417–537 nm and 4.17–4.23 eV by altering the γ-radiation dose with PLQYs realized in the range of 10–24%. Lifetimes of these samples are in the range of 1.69–2.68 and 6.82–34.88 ns for the fast- and slow-decaying components, respectively.